ظاهرة الحذف في سورتي هود ويس ؛ دراسة نحوية وبلاغية - محمد نور بن حسين (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2006)
The objective of this thesis is to study the phenomenon of Hadhf in two Suras, Hud and Yasin. This thesis examines the grammatical and rhetorical aspects of Hadhf in the Holy Qur’an generally and in Two Suras particularly. The grammatical study is to find out the indications and causes of Hadhf, while the rhetorical study is to highlight the significance of Hadhf in the Holy Qur’an. In this regard, this study strives to identify the occurrence of Hadhf in the Holy Qur’an by utilizing a descriptive and analytical approach. This study puts forward the necessity of understanding both the Hadhf phenomenon together with the rhetorical purposes at Qur’anic suras. It is hoped that this study will lead to a deeper understanding of the significance of this phenomenon so that comprehending the Holy Qur’an would become more effective and systematic.